Recommendations on RBC Transfusion Support in Children With Hematologic and Oncologic Diagnoses From the Pediatric Critical Care Transfusion and Anemia Expertise Initiative. (September 2018) - Steiner, Marie E.; Zantek, Nicole D.; Stanworth, Simon J.; Parker, Robert I.; Valentine, Stacey L.; Lehmann, Leslie E.; Josephson, Cassandra D.; Bateman, Scot T.; Luban, Naomi L. C.
Abstract : Objectives: To present the recommendations and supporting evidence for RBC transfusions in critically ill children with hematologic and oncologic disease from the Pediatric Critical Care Transfusion and Anemia Expertise Initiative. Design: Consensus conference series of international, multidisciplinary experts in RBC transfusion management of critically ill children. Methods: The panel of 38 experts developed evidence-based and, when evidence was lacking, expert-based clinical recommendations and research priorities for RBC transfusions in critically ill children. The hematologic/oncologic subgroup included seven experts. Electronic searches were conducted using PubMed, EMBASE, and Cochrane Library databases from 1980 to May 2017. Agreement was obtained using the Research and Development/UCLA Appropriateness Method. Results were summarized using the Grading of Recommendations Assessment, Development, and Evaluation method. Results: The hematologic/oncologic subgroup developed 14 recommendations (seven clinical, seven research); all achieved greater than 80% agreement. In patients with sickle cell disease, Transfusion and Anemia Expertise Initiative recommends: 1) RBC transfusion to achieve a target hemoglobin concentration of 10 g/dL rather than hemoglobin of less than 30% prior to surgical procedures requiring general anesthesia and 2) exchange transfusion over simple (nonexchange) transfusion if the child's condition is deteriorating (based on clinical judgment), otherwise a simple, nonexchange RBC transfusion is recommended. There is insufficient evidence to make recommendations on transfusion thresholds for patients with sickle cell disease prior to minor procedures, with acute stroke or with pulmonary hypertension. For patients with oncologic disease or undergoing hematopoietic stem cell transplant, a hemoglobin concentration of 7–8 g/dL is recommended. Due to lack of evidence, research is needed to clarify the appropriate transfusion thresholds in these patients. Conclusions: Transfusion and Anemia Expertise Initiative developed specific pediatric recommendations regarding RBC transfusion management in critically ill children with sickle cell disease, oncologic disease, and hematopoietic stem cell transplant and recommendations to help guide future research priorities. Abstract : Supplemental Digital Content is available in the text.